Annelida (Oligochaeta and Aphanoneura) from the Natural Reserve of Isla Martín García (Upper Río de la Plata estuary, Argentina): biodiversity and response to environmental variables - César, Inés Irma (2014)
The Island of Martín García located in the Upper Río de la Plata, to the south of the Uruguay River-is an outcropping of the crystalline basement. Fourteen sampling sites were selected, five along the littoral section of the island and nine in inland ponds. Four major environmental variables were measured: water temperature, dissolved oxygen, electrical conductivity, and pH. A total of 34 species of Oligochaeta and Aphanoneura were found, 30 belonging to Naididae plus one species each of the Narapidae, Lumbricidae, Enchytraeidae, and Aeolosomatidae. The thirteen most frequent species were: A. leydigi (30%), N. bonettoi (13%), L. hoffmeisteri (11%), N. variabilis (10%), S. trivandrana (6.5%), A. pigueti (5.6%), D. sawayai (4.5%), D. digitata (3.5%), C. diastrophus (2.7%), A. costatus (2.5%), P. longiseta (2.0%), Enchytraeidae (1.5%), and A. p. paraguayensis (1.4%). UPGMA clustering of species based on their occurrence in different ecological conditions revealed two main species groups. Canonic-correspondence analysis (CCA) was conducted with the 15 most frequent and abundant species in the 9 sampling sites and the 4 environmental variables. Results from the CCA revealed that the order of fluctuation of the environmental variables during the sampling period was, from the greatest to the least: dissolved oxygen, conductivity, pH, and water temperature. Approximately 97.6% of the correlations between species and environmental variables were expressed on axis 1 of the ordination diagram. Species richness correlated with the four environmental variables in the following order, from the weakest to the strongest: water temperature, pH, electrical conductivity, and dissolved oxygen.